EFL TEACHERS AND STUDENTS’ VOICES ON EMERGENCY REMOTE TEACHING IN SPEAKING CLASS - Riyani, Riyani; Febriani, R. Bunga; Faridah, Didih; Syafryadin, Syafryadin (Premise: Journal of English Education and Applied Linguistics, 2023)
Adapting to the current condition of the COVID-19 pandemic has become crucial to keep teaching-learning going since the shift of traditional classes to emergency remote teaching. Meanwhile, teachers and students have difficulties implementing emergency remote teaching(ERT), especially in speaking classes. Thus, this present research aimed to explore the teachers' and students voices on emergency remote teaching in speaking classes to contribute to the previous related studies by employing a phenomenological study, as the research design, at a private university in Ciamis, Indonesia. The data were collected by distributing close-ended questionnaires and semi-structured interviews with 15 EFL students and 2 EFL teachers who have experienced emergency remote teaching in speaking class. The results of this study revealed that speaking class-based emergency remote teaching could be carried out interchangeably through synchronous and asynchronous platforms, namely Zoom Meeting; Google Meet; Google Classroom; and Video Recording, along with its benefits and drawbacks. Furthermore, the successful implementation of emergency remote teaching could not be separated from the solutions to overcome the problems and the school support in training teachers and students to implement emergency remote teaching and become well-trained in utilizing technology.